Further clarification on the variants of double-outlet right atrium - Mani Ram Krishna; Robert H Anderson (Wolters Kluwer Medknow Publications, 2021)
Uniatrial but biventricular atrioventricular connection is a rare congenital cardiac abnormality where the left atria-ventricular connection is absent and the right atrio-ventricular connection straddles the crest of the muscular ventricular septum. This anomaly has been referred to as double outlet right atrium and the atrio-ventricular valve as a common atrioventricular valve in the past.In the absence of a primary atrial septal defect, the atrio-ventricular junction is not a common junction and the valve cannot hence be described as a common trio-ventricular valve. We demonstrate this paradox by an illustrative case and contrast this with two other cases where a common atrio-ventricular valve was predominantly committed to the right atrium.